Combination of Infective Endocarditis and Covid-19 Infection in a Young Patient - E. Yu. Ponomareva; N. A. Kosheleva (SINAPS LLC, 2021)
Infective endocarditis of the native mitral valve with multiple cardioembolic cerebral infarctions and myocardial infarctions against the background of a severe new coronavirus infection caused an unfavorable outcome in a young woman. The reasons for this were both the late diagnosis of IE (untimely performance of transthoracic echocardiography) and the synergy of the pathogenetic mechanisms of two serious diseases, which was most clearly manifested in the development of hemorheological disorders, damage to the myocardium, lungs and brain.